Prevalence of hearing impairment and language and cognition delay in very low birth weight babies and their risk factors - Saugata Chaudhuri (Manipal College of Medical Sciences, Pokhara, 2021)
Background: Very low birth weight infants are at increased risk of language, cognition delay and also hearing impairment disorder. Identification is essential for early intervention.